Developing Self-regulated Learning Skills in University Students Studying in the Open and Distance Learning Environment by Using KWL Method - D. V. M. De Silva (Commonwealth of Learning, 2020)
Open and Distance Learning (ODL) is considered an important strategy for increasing educational access. However, students learning in ODL environments face many challenges. Studies have indicated that students with self-regulated learning (SRL) skills are more likely to succeed in ODL environments. Studies have demonstrated that through instructional strategies, tutors can teach and help improve SRL skills. This development of SRL skills may lead to reduced drop-out rates. To examine the suitability of SRL skills development strategies, the researcher of this study utilised a KWL (What I Know, What I Want to Know, What I Learned) method in the ODL environment in Sri Lanka to help develop SRL skills in university students. This study adopted an action research approach, and twenty-four (24) Bachelor of Education students and three (03) educators at the Open University of Sri Lanka were the participants. Zimmerman & Moylan's (2009) self-regulated cycle of learning model was used for the intervention. A Motivated Strategies for Learning Questionnaire (MSLQ,1991) was administered to measure students' SRL skills. Observations, reflections, and focus group discussions were used to collect qualitative data. The study's findings indicated that the KWL method contributed to the improvement of self-regulated learning skills among student participants.